Protection for the Vulnerable: How Unaccompanied Minors From El Salvador, Guatemala, and Honduras Can Qualify for Asylum in the United States - Melissa Weiss (Washington University Law Review, 2015)
In the past few years there has been an increased number of unaccompanied minors coming to the United States from El Salvador, Guatemala, and Honduras. They make a long and often dangerous journey to flee violence in their home countries and seek protection in the United States. One way these children may seek protection is by claiming asylum. The definition of asylum in the United States provides for protection if the applicant has suffered or fears they will suffer persecution due to: race, religion, nationality, membership in a particular social group, or political opinion. Children coming to the United States from El Salvador, Guatemala, and Honduras likely cannot qualify for asylum unless they have suffered persecution based on membership in a particular social group. Although the Board of Immigration Appeals and the courts have tried to define membership in a particular social group, it is vague and ambiguous. The Board of Immigration currently requires that the group under which the applicant is claiming to be a member share a common immutable characteristic, is particular and socially distinct. This note examines the Board of Immigration Appeals definition of particular social group. It discusses the situation of children fleeing from El Salvador, Guatemala, and Honduras and proposes a particular social group under which the children may qualify for asylum. It analyzes the proposed group and explains why it would be likely to succeed. The note further considers alternative options for protecting the unaccompanied minors who have fled by looking at international conventions that have been adopted in other parts of the world, such as Africa and Latin America.
Keywords: Asylum Law; Unaccompanied minors; Gang violence; Honduras; El Salvador; Guatemala; Particular social group; Refugee